Optimal Opportunistic Monetary Policy in A New-Keynesian Model - Massimiliano Marzo; Ingvar Strid; Paolo Zagaglia (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
The present paper compares the performance in terms of second order accurate welfare of opportunistic non-linear Taylor rules and with respect to traditional linear Taylor rules. The macroeconomic model representing the benchmark for the analysis includes capital accumulation (with quadratic costs of adjustment), price rigidities (quadratic approach), along the standard New-Keynesian approach. The model is solved up to second order approximation and welfare is evaluated according to several criteria (conditional to the non-stochastic steady state, unconditional, and according to a linear ad hoc function). The results show that: (i) the opportunistic rule is a Pareto improvement with respect to other monetary policy rules traditionally considered in the literature; (ii) the computation of welfare costs reveals that the burden of adjustment is almost entirely on labor supply fluctuations;(iii) increasing the degree of price rigidities and the degree of competition in the final goods markets, makes the opportunistic rule even more preferable with respect to the alternatives. Business Cycle statistics for the model with opportunistic rule show a large volatility in labor supply, with a limited volatility for the nominal interest rate.
Keywords: 330; Inflationsbekämpfung; Geldpolitik; Regelbindung versus Diskretion; Taylor-Regel; Preisrigidität; Neoklassische Synthese; Theorie; USA